Avaliação da atividade alelopática, antioxidante, fotoprotetora e análises fitoquímicas do extrato de folhas de Euterpe edulis Martius - Mariquito, Anderson (2020)
Euterpe edulis Martius (Palmeira Juçara) is a native Brazilian palm (Arecaceae), about which there are very few reports regarding its biological activity and chemical composition. The objective of this research was to perform bioprospecting and evaluate the biological potential of the ethanolic extract of leaves from E. edulis leaves and its fractions: hexane, dichloromethane, ethyl acetate, butanol and aqueous, determining the chemical classes present in these extracts. The germination index (GI), initial growth, enzymatic activity, content of chloroplast pigments and starch in seeds and seedlings of Lactuca sativa L. (lettuce) and Panicum maximum Jacq were evaluated at concentrations of 0.0, 0.25, 0.50, 0.75 and 1.0 mg/mL of these extracts and their fractions. Interpolating through a regression analysis, we observed that the hexane 0.75 mg mL and aqueous 1.0 mg/L fractions showed better results in relation to the GI variables (51.2 and 69.5%), germination speed index (3.45 and 4.55), allelopathy index (39.90 and 18.55) and root growth (2.87 and 3.11 cm), respectively. There was a significant difference in enzymatic activity for all treatments with the hexane fraction 0.75 mg/mL on lettuce and on colonization grass and for most aqueous fractions 1.0 mg/mL, with the exception of catalase on lettuce and peroxidase on colonial grass. Chloroplast pigments, as well as starch, increased significantly, but it was not enough to protect grass that had IG and initial growth negatively affected. The contents of phenolics, tannins and total flavonoids were evaluated. For the ethanolic extract and its polar fractions, the HPLC test was performed and for the non-polar fractions the GC-MS. The results obtained for the contents of phenols and tannins were significant for the crude extract and all its fractions, being thak acetate fraction having showed the best results. The best results for the phenolic content were obteined for the aqueous fraction. In the HPLC analysis, the analyzed patterns were not found. The GC-MS of the hexane and dichloromethane fraction demonstrated the presence of 3,7,11,15-Tetramethyl-2-hexadecen-1-ol (Phytol) and vitamin E. The antioxidant activity was significant for the crude extract and its fractions in all concentrations for the ABTS, DPPH, FRAP and TAC-Phosphomolybdenum assays, having a dose-dependent effect. In the maximum absorbance test, the crude extract and its fractions could be used in a possible composition in formulations of a sunscreen, since antioxidants were found in large quantities and would act as a complement to sunscreens. The results allow concluding a possible sustainable use of E. edulis leaves due to their allelopathic potential their antioxidant activity and sun protection factors.